lncRNA ACVR2B-AS1 modulates thyroid cancer progression by regulating miR-195-5p - Tianshi Qin; Chengqiang Lei; Henghua Xiao; Jun Yang; Qiong Luo; Lingli Hu; Fang Chen; Manlong Long; Huayi Zhang (Discover Oncology)
Abstract Background lncRNAs are key regulators in thyroid cancer (TC). While lncRNA ACVR2B-AS1 has been proposed as a potential TC biomarker, its role remains underexplored. This study aims to clarify its clinical significance in TC and investigate its molecular mechanism. Materials and methods qRT-PCR was used to assess the expression of ACVR2B-AS1 in TC tissues and cell lines. Kaplan–Meier survival curves and Cox regression were utilized to assess the prognostic value of ACVR2B-AS1 expression. The interaction between ACVR2B-AS1 and miR-195-5p, as well as their effects on cell viability, migration, and invasion, were evaluated using dual-luciferase reporter assays, CCK-8 assays, and Transwell assays. Results ACVR2B-AS1 was significantly upregulated in TC tissues and cell lines, and its expression correlated with TNM stage and lymph node metastasis. Elevated ACVR2B-AS1 levels were associated with poor survival outcomes, and it was identified as an independent risk factor for TC progression. A direct regulatory relationship was established between ACVR2B-AS1 and miR-195-5p, with ACVR2B-AS1 negatively regulating miR-195-5p, thereby promoting TC cell proliferation, migration, and invasion. FGF2 was predicted and validated as a target gene of miR-195-5p. Conclusion lncRNA ACVR2B-AS1 shows potential as a prognostic marker in TC and may regulate tumor progression through the miR-195-5p/FGF2 axis, offering new insights for TC diagnosis and treatment.